Long-distance impact of Iceland plume on Norway’s rifted margin - Koptev, Alexander (Sci Rep, 2017)
Results of a 3D modeling study inspired by recent seismic tomography of the Northern Atlantic mantle suggest that a complex pattern of hot mantle distribution with long horizontal flows originating from the Iceland mantle plume has been the norm in the geological past. In the Northern Atlantic the Iceland plume has a strong long-distance impact on intraplate deformation affecting both onshore and offshore parts of Norway’s rifted margin. As a result, this margin is characterized by large magnitude differential topography sustained over at least several tens of Myr. Here we use high-resolution 3D thermo-mechanical modeling to demonstrate that the long-distance plume impact can be explained by its fast lateral propagation controlled by pre-existing lithosphere structures. Numerical models show that these structures strongly affect the style of horizontal flow of plume head material. This results in long-distance propagation of hot material emplaced at the lithosphere-asthenosphere boundary causing long-wavelength anomalies in onshore topography of Norway’s rifted margin. Short-wavelength offshore topographic domes are likely caused by joint occurrence of plume-related thermal perturbations and gravitational forces related to plate thickening (ridge push). Our 3D modeling brings together plume impingement, spreading ridge dynamics, and the formation of anomalous intraplate structures offshore Norway in one scenario.